« Aux ordres de l’époux obéir, c’est le droit essentiel des épouses » : le mariage dans les écrits de la princesse Franciszka Urszula Radziwiłł (1705-1753) - Judkowiak, Barabara (AMU Press, 2011)
This article deals with the issue of love, marriage and motherhood, which dominates the work of the first Polish female writer to be at once both a poetess and a dramatist. It offers a reconstruction of the biographical context that strongly influences many of Radziwiłłowa’s utterances on this subject and sheds light on more general matters, such as the juridical and social situation of women in the Polish-Lithuanian Commonwealth.